Epidemiology of and risk factors for mortality due to carbapenemase-producing organisms (CPO) in healthcare facilities. (April 2021) - Zhao, S.; Kennedy, S.; Perry, M.R.; Wilson, J.; Chase-Topping, M.; Anderson, E.; Woolhouse, M.E.J.; Lockhart, M.
Summary: Background: Carbapenemase-producing organisms (CPO) have been largely responsible for the extensive spread of carbapenem resistance, and their prevalence is increasing in many parts of the world. Aim: To evaluate clinical and molecular epidemiology and mortality associated with CPO among patients. Methods: All CPO from clinical and long-term healthcare surveillance cultures across Scotland in 2003–2017 were reviewed retrospectively. Polymerase chain reaction was used to detect genes coding for carbapenemases. A generalized linear mixed model was used to identify risk factors for mortality. Findings: In total, 290 individuals with CPO were identified. The overall incidence increased over time ( P <0.001) from 0.02 to 1.38 per 100, 000 population between 2003 and 2017. A total of 243 distinct CPO isolates were obtained from 269 isolations in 214 individuals with available metadata. The majority of the isolates were Enterobacterales (206/243, 84.8%), and Klebsiella pneumoniae (65/206, 31.6%) and Enterobacter cloacae (52/206, 25.2%) were the most common species. VIM (75/243, 30.9%) and NDM (56/243, 23.0%) were the most common carbapenemases. The crude 30-day mortality rate was 11.8% (25/211), while the case fatality rate was 5.7% (12/211). Age >60 years [adjusted odds ratio (aOR) 3.36, 95% confidence interval (CI) 1.06–10.63; P =0.033], presence of non-fermenters (aOR 4.88, 95% CI 1.64–14.47; P =0.005), and systemic infection or organ failure (aOR 4.21, 95% CI 1.38–12.81; P =0.032) were independently associated with 30-day mortality. Conclusion: The incidence of CPO in Scotland is low but increasing. Awareness is required that inpatients aged >60 years, patients with systemic infection or organ failure, and patients presenting with non-fermenters are at higher risk of death from CPO.